Analysis of The Effectiveness of Cloud-Based Operations Management in Digital SMES - Febriana, Widia; Yoga Sumadewa, I Nyoman; Anggriani, Rini; Zahrah, Zahrah (Sumber Belajar Sejahtera, 2025)
The rapid development of digital technology has encouraged Micro, Small and Medium Enterprises (MSMEs) to adopt cloud-based operation management systems. This study aims to analyze the effectiveness of cloud technology implementation in supporting the operational activities of digital-based MSMEs, especially in the aspects of work efficiency, decision making, and adaptation to market changes. The method used is a qualitative approach with case studies on several MSMEs that have implemented cloud systems in their operational management. Data were collected through in-depth interviews, direct observation, and documentation of operational activities. The results show that the use of cloud-based systems has a positive impact on increasing operational efficiency, data transparency, and flexibility in resource management. In addition, MSMEs that utilize this technology tend to be more adaptive to market dynamics and faster in responding to customer needs. However, there are also some challenges, such as limited digital literacy and dependence on a stable internet connection. In conclusion, cloud-based operation management is an effective solution for digital-based MSMEs, although a sustainable mentoring and training strategy is needed for optimal and sustainable implementation